Fit-for-purpose characterization of air-liquid-interface (ALI) in vitro exposure systems for e-vapor aerosol. (August 2022) - Zhang, J.; Doshi, U.; Wolz, R.L.; Kosachevsky, P.; Oldham, M.J.; Gillman, I.G.; Lee, K.M.
Abstract: Air-liquid-interface (ALI) exposure systems deliver aerosol to the apical surface of cells which mimics the in vivo inhalation exposure conditions. It is necessary, however, to quantify the delivered amount of aerosol for ALI-based in vitro toxicity assessment. In this study, we evaluated two commercially available ALI exposure systems, a Vitrocell® Ames 48 (Ames 48) and a Vitrocell® 24/48 (VC 24/48), and the Vitrocell® VC1/7 smoking machine using a cig-a-like cartridge-based e-vapor device with a prototype formulation (containing 4% nicotine by weight). We characterized aerosol particle-size distribution, aerosol mass, and major chemical components (nicotine, propylene glycol, and glycerol) at the generation source and verified the repeatability of the aerosol generation. We determined aerosol delivery at the ALI by gravimetric analysis of mass collected on Cambridge filter pads and analytical quantitation of the buffer medium which showed that both aerosol mass and nicotine to an exposure insert linearly increased up to 400 puffs. The delivered aerosol mass covered a wide range of 0.8–3.4 mg per insert in the Ames 48 with variability (relative standard deviation, RSD) up to 12% and 1.1–6.4 mg per insert in the VC 24/48 with variability up to 15%. The delivered nicotine ranged approximately up to 200 μg per insert in both exposure systems. These results provided operation and aerosol delivery information of these ALI exposure systems for subsequent in vitro testing of e-vapor aerosols. Highlights: We characterized an Ames 48 and a VC 24/48 for e-vapor aerosol toxicity evaluation. The Ames 48 delivered 0.8 – 3.4 mg aerosol per insert under testing conditions. The VC 24/48 delivered 1.0 – 6.4 mg aerosol per insert under testing conditions. Delivered nicotine ranged up to approximately 200 μg per insert in both exposure systems. The PSD as measured by cascade impactor were comparable prior to and after VC 24/48 or Ames 48.